Innate immune receptors as mediators of systemic inflammation and pathogenesis of malaria - Gazzinelli, Ricardo (Henry Stewart Talks, 2013)
Malaria and Plasmodium parasites, Innate immune receptors, Plasmodium recognition by host innate immune receptors, and in particular by Toll-like Receptors (TLRs), Excessive activation of TLRs and pathogenesis of malaria inflammasome, Caspase-1 induced inflammation and fever in malaria, Use of a TLR antagonist to treat experimental cerebral malaria